Medical pharmacology : principles and concepts - Goth, Andres (Toronto, Canada : The C.V. Mosby Company, 1984)
The eleventh edition of Medical Pharmacology is essentially a new book. About 20 chapters have been either completely rewritten or significantly revised by contributors who are experts in their fields. All other chapters have also been brought up to date.
Section One. general aspects of pharmacology -- Section Two. Drug effects on the nervous system and neuroeffectors -- Section Three. Psychopharmacology -- Section Four. Depressants and stimulants of the central nervous system -- Section Five. Anesthetics -- Section Seven. Drug effects on the respiratory and gastrointestinal tracts -- Section Eight. Drugs that influence metabolic and endocrine functions -- Section Nine. Chemotherapy -- Section Ten. Principles of immunopharmacology -- Section Eleven. Poisons and antidotes -- Section Twelve. Drug interactions -- Section Thirteen. Prescription writing and drug compendia.
Includes bibliographical references and index.
Keywords: PHARMACY